The influence of sardine consumption on the omega-3 fatty acid content of mature human milk - Patin, Rose V.; Vítolo, Márcia R.; Valverde, Mara A.; Carvalho, Patrícia O.; Pastore, Gláucia M.; Lopez, Fábio Ancona [UNESP] (Fundacao Sociedade Brasileira de Pediatria, 2006)
Objectives: The purpose of this study was to investigate what effect the ingestion of sardines, rich in omega-3 series polyunsaturated fatty acids, has on the composition of breastmilk. Methods: This was a prospective study of 31 nursing mothers under observation at the Hospital Guilherme Álvaro. Each was given 2 kg of fresh sardines twice with a 15-day interval. Milk was sampled and a 24-hour dietary recall questionnaire was applied on days 0, 15 and 30. Milk was assayed for fatty acid content by gas chromatography. Statistical analysis of the results was performed using nonparametric tests with significance set at p < 0.05. Results: The results demonstrate that the nutritional intake of the nursing mothers was adequate at all three sample points. With regard to the omega-3 series fatty acid content of the breastmilk, it was observed that regular consumption and shorter intervals between ingestion and milk collection resulted in higher concentrations of docosapentaenoic acid and docosahexaenoic acid at 15 and 30 days into the study. Fatty acids from the omega-3 and omega-6 series exhibited a significant correlation, r 2 was 0.58 and 0.59 at 15 and 30 days, respectively. Conclusion: These results suggest that incorporating fish into the diets of nursing mother during lactation, in the form of 100 g of sardines two or three times a week, contributes to an increase in omega-3 series fatty acids. Copyright © 2006 by Sociedade Brasileira de Pediatria.
Keywords: Breastfeeding; Breastmilk; Docosahexaenoic acid (DHA); Fish consumption; Fish intake; Human milk; Lactation; Omega-3 fatty acids; Polyunsaturated fatty acids; docosahexaenoic acid; docosapentaenoic acid; omega 3 fatty acid; omega 6 fatty acid; adult; breast feeding; breast milk; controlled study; dietary intake; fatty acid analysis; female; fish; food intake; gas chromatography; human; lactation; milk level; nonparametric test; nutrient concentration; nutrient content; nutritional assessment; nutritional value; questionnaire; statistical analysis; Animals; Breast Feeding; Energy Intake; Fatty Acids, Omega-3; Female; Fishes; Gestational Age; Humans; Milk, Human; Nutritional Status; Prospective Studies; Statistics, Nonparametric